(untitled) (مجلة إحالات, 2026)
Through this study we aim to read the text of Zahana letter from prison to find a problematic way out of memory. This consideration seems to be more difficult if it is not withdrawn through the issue of duty as a top practice, not to mention that the thought of working after the Secretariat puts us in the context of the problem of conscience and responsibility. These concepts come from the data of the discourse, which is interpreted in its more open version of the Algerian revolutionary heritage, The questioning of the moment of Zahana is more likely to be rooted in a return to the reading of the message of a thought condition that grants the transition between the problem of self and memory. How can an approach be developed that exhaust these data?